2004
DOI: 10.1002/mds.20294
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a disorder of locomotor timing in Huntington's disease

Abstract: Disturbances of walking have been described in people with Huntington's disease (HD), although the nature of the deficits have not yet been well defined. The purpose of this investigation was to determine whether people with HD have a deficit in the regulation of footstep timing during walking. The footstep patterns of 30 people with HD and 30 matched comparisons were measured at self-selected slow, preferred, and fast speeds. Subjects were also instructed to match their footsteps to auditory metronome cues se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
5
43
0
Order By: Relevance
“…This study demonstrates that gait cadence is also decreased when measured at home. In addition, the values of at-home steps per minute for controls and participants with HD are very similar to values measured in clinic [16][17][18][19].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This study demonstrates that gait cadence is also decreased when measured at home. In addition, the values of at-home steps per minute for controls and participants with HD are very similar to values measured in clinic [16][17][18][19].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have also shown that gait cadence is decreased in HD through in-clinic evaluations [16][17][18][19]29]. This study demonstrates that gait cadence is also decreased when measured at home.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Implementation of a targeted multidisciplinary rehabilitation program into the Huntington's disease population is anticipated to reduce dependence on the health system due to a reduction in the utilisation of health services as a result of a reduction in fall-related injuries, and may delay placement into residential and end-stage facilities by encouraging and maintaining patient independence. Huntington's disease is characterised by progressive cognitive, affective and motor deterioration over a 15-25 year period, together with a spectrum of associated physical deficits including postural instability [6][7][8][9][10] , gait impairments [11][12][13][14][15][16] and lean and fat tissue loss 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric muscle strength changes in the upper and lower body showed highly significant, progressive increases in total group muscle strength, and significant increases for female (p<0.03) and male (p<0.02) subgroups, in all exercises after 9 months intervention (p<0.0005; Figure 40). [21], and separately for female [11] and male [10] sub-groups to indicate gender response). Highly significant increases in muscle strength were achieved for each of the above exercises after 9 months intervention (p<0.0005).…”
Section: Mean Insulin C-peptide Concentrationmentioning
confidence: 99%